EFEKTIVITAS VARIASI DOSIS KALSIUM HIPOKLORIT (Ca(OCl)2) DALAM MENURUNKAN KOLONI Salmonella sp DAN BAKTERI Coliform PADA LIMBAH CAIR RUMAH POTONG HEWAN PENGGARON SEMARANG - Maysaroh Nur Istikomah; Budiyono Budiyono; Yusniar Hanani Darundiati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Slaughterhouse is one of the public service units thatpotential to produce liquid waste with the content of pathogenic bacteria that harmful to health.Concentration of Salmonella sp found in effluen wastewater treatment plant Penggaron Slaughterhouse as much as 6,1 x 104 CFU, the amount still in the infective dose range to cause disease. Chlorination with calcium hypochlorite can reduce concentration of pathogenic micoorganisms. This study aims to determine the effectiveness of calcium hypochlorite in reducing number of Salmonella sp colony and number of Coliform in wastewater Penggaron Salughterhouse. This research method is quasi experiment and pre-test design and post-test with control group. Statistical analysis using Kruskall-Wallis test. The results of the study before the treatment with calcium hypochlorite showed the number of Salmonella sp as much as 7.9 x 104 CFU while the number of Coliform bacteria was 2400 MPN / 100 ml. Addition calcium hypochlorite as much as 10 mg/l, 15 mg/l, 20 mg/l, 25 mg/l and 30 mg/l with 5 repetitions. Addition calcium hypochlorite decreased the number of Salmonella sp colony to 9.8 x 103 CFU; 1.0 x 104 CFU; 5.5 x 103 CFU; 1.8 x 104 CFU; 1.2 x 104 CFU while the number of Coliform bacteria decreased to 2100 MPN / 100 ml, 2240 MPN / 100 ml, 1544 MPN / 100 ml, 2100 MPN / 100 ml, 2020 MPN / 100 ml. Statistical analysis showed that there was no significant difference in reducing number of Salmonella sp colonies and the number of Coliform bacteria (p>0,05) after treatment with various doses of calcium hypochlorite. There is no effective dose of calcium hypochlorite because it has not been able to decrease the number of Salmonella sp colony and number of Coliform bacteria under the quality standard.